Pembelajaran yang Menumbuhkan Sikap Disiplin Siswa - Moch Yunus; Sholeha, Siti Amilus (At- Ta'lim : Jurnal Pendidikan, 2020)
This study was conducted aimed at finding a picture of learning that fosters the discipline of students in full day schools with heterogeneous backgrounds. After obtaining this description, then a learning model is described which fosters student discipline. Learning that fosters student discipline in the context of a full day school: Phenomenological Study at SMP Bhakti Pertiwi Paiton Probolinggo, East Java.